2015
DOI: 10.1653/024.098.0419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a PathogenicBeauveria bassiana(Hypocreales: Cordycipitaceae) Strain on Detoxifying and Protective Enzyme Activities inXylotrechus rusticus(Coleoptera: Cerambycidae) larvae

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
9
19
0
Order By: Relevance
“…The three enzymes work synergistically, keeping the ROS level low and prohibiting oxidative damage. The overall activity trends were consistent with previous research [38,[44][45][46][47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The three enzymes work synergistically, keeping the ROS level low and prohibiting oxidative damage. The overall activity trends were consistent with previous research [38,[44][45][46][47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 91%
“…SOD catalyzes the dismutation of superoxide anion to hydrogen peroxide, which is subsequently detoxified to oxygen and water by catalase, ascorbate peroxidase or GST. Previous studies have demonstrated that, after fungal infection, protection systems of insects are activated to ward off infection and to maintain the normal physiological activities [38][39][40][41][42]. In our study, a significant increase in CAT, APOX and SOD activities were noticed in larvae of Spodoptera litura after treatment with ethyl acetate extract of Schizophyllum commune.…”
Section: Discussionsupporting
confidence: 60%
“…The activities of GST and CAT were significantly inhibited, indicating that compound 2 could inhibit the activity of these detoxifying and protective enzymes after entering into the larva of H. armigera , making it difficult to be metabolized, and thus, enhancing the toxicity to H. armigera. Some studies had shown that the activities of GST and CAT in the insect were inhibited after treatment by pesticides [ 20 ]. Besides antioxidant enzymes, insects also have other antioxidant mechanisms, such as trehalose and α-tocopherol, which also play an active role in oxidative stress [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ding et al [38] and Jia et al [58] observed the similar trend in GST activity after exposure to fungus B.…”
Section: Discussionmentioning
confidence: 63%